2021
DOI: 10.3389/fnbeh.2021.717847
|View full text |Cite
|
Sign up to set email alerts
|

Family and Community Support, Brain-Derived Neurotrophic Factor, and Cognitive Performance in Older Adults: Findings From the Health, Wellbeing and Aging Study Population-Based Cohort

Abstract: Background: Social networks can modulate physiological responses, protects against the detrimental consequences of prolonged stress, and enhance health outcomes. Family ties represent an essential source of social networks among older adults. However, the impact of family support on cognitive performance and the biological factors influencing that relationship is still unclear. We aimed to determine the relationship between family support, cognitive performance and BDNF levels.Methods: Cross-sectional data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that community support has a positive effect on cognitive function of the elderly; in particular, functional support and emotional community support are very important to the cognitive function of the elderly ( Hiroshi et al, 2019 ; Souza-Talarico et al, 2021 ). Functional community support is mainly reflected in medical service, community infrastructure construction, community environment construction, and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that community support has a positive effect on cognitive function of the elderly; in particular, functional support and emotional community support are very important to the cognitive function of the elderly ( Hiroshi et al, 2019 ; Souza-Talarico et al, 2021 ). Functional community support is mainly reflected in medical service, community infrastructure construction, community environment construction, and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, a good lifestyle can slow cognitive decline ( Kang et al, 2021 ), such as physical activity ( Lü et al, 2016 ) and fitness ( Daimiel et al, 2020 ) as well as good nutrition ( Smith and Blumenthal, 2016 ). On the contrary, smoking increases the risk of cognitive impairment in the elderly ( Souza-Talarico et al, 2021 ). In addition, maintaining one’s interests can also help maintain a state of normal cognition ( Iwasa et al, 2012 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cross-sectional data from our research group revealed that the poorer the family support, the lower the cognitive performance (global cognition, verbal fluency and digit span) 12 . However, these findings were drawn from a cross-sectional analysis, precluding any meaningful interpretation of the impact of family functioning on the probability of cognitive decline over time 12 .…”
Section: Introductionmentioning
confidence: 78%
“…However, unlike the present study, the authors analyzed family relationships rather than family functioning, which potentially explains the disparities in findings. In a cross-sectional analysis of the SABE cohort which included only older adults aged 60–64 years, functional family support, but not structural support (number of individuals living with older adult), was found to be associated with higher scores on the MMSE, verbal fluency and digit span tests 12 . Moreover, the authors found that, unlike receiving social support, providing the community with support services was associated with better cognitive performance 12 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation